The Role of Wordwall in Improving Interactive Learning Quality: An Analisis of Empirical Studies through Systematic Literature Review - Dhesi Purnamasari; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This study investigates the role of Wordwall in enhancing the quality of interactive learning using a Systematic Literature Review (SLR) approach based on PRISMA guidelines. From an initial pool of 81 studies, 40 empirical articles (international and national) were selected for synthesis. The results indicate that Wordwall significantly contributes to increased learning motivation, outcomes, engagement, collaboration, communication, and concept mastery across educational levels. The findings affirm the relevance of digital gamification tools like Wordwall in supporting 21st-century education.